Right lower quadrant abdominal mass: A case report - Anup Chalise; Lok Bahadur Kathayat; Prabhat Poudel; Ashish Prasad Rajbhandari; Rabin Koirala (Clinical Case Reports, 2022)
Abstract Right lower quadrant mass in the abdomen has many causes, but gastric perforation is rare. We discuss a 65‐year‐old lady who presented with a history of pain in her abdomen followed by swelling in her right lower abdomen. During the evaluation, a diagnosis of gastric perforation was made.